Enrichment a critique of commodities - Boltanski, Luc 1940-; Esquerre, Arnaud 1975- (Polity, 2020)
"This book offers a major new account of modern capitalism and of the ways in which value and wealth are created today."
"First published in French as Enrichissement, (c) Editions Gallimard, Paris, 2017." - Verso
Includes bibliographical references and index
Keywords: Kapitalismus; Handel; Wert; Gut -- Wirtschaft; Frankreich; Commercial products / Europe, Western; Capitalism / Europe, Western; Cultural property / Economic aspects / Europe, Western; Europe, Western / Commerce; Europe, Western / Economic conditions